Hydraulic Performance Assessment and Upgrading of The Tswelopele Village (Gauteng) Water Distribution Network - Magabatela, Jonathan (University of the Witwatersrand, Johannesburg, 2024)
The hydraulic performance assessment of a water distribution network can reveal critical information that might help to address challenges experienced within that network. This study investigated the hydraulic performance and upgrading of the Tswelopele water distribution network to accommodate additional 35 yard connections. In line with the main objective of the study, the following were addressed, (1) modelling and simulating in EPANET the existing Tswelopele water distribution network and ascertaining the nodes experiencing below minimum pressures, (2) determining and incorporating upgrades required to accommodate current and future water demands, (3) optimization of the proposed upgraded water distribution network, initially using trial and error typically employed by industry and then using Wadiso software and (4) comparison of results obtained using the two approaches. Tswelopele Village comprises 89 households, and only 54 are connected to the existing water distribution network. The existing water distribution network was refurbished in 2015 but some households which are part of the water distribution network are still experiencing erratic water supply. A model of the existing network was prepared and simulated in EPANET. The analysis results indicated that only one node had a pressure value below the normally minimum accepted of 20m, but it was more than the minimum allowable pressure of 15m. Therefore, it is suspected that the water challenges might not be due to low pressure but to other reasons such as leakages, partially open valves or illegal connections. To accommodate the additional 35 households, an upgrade of the network incorporating future water demands was proposed. Optimization by trial and error was employed as per usual industry approach and was checked by optimization with Wadiso software. A comparison of the results revealed that based on July 2023 pipe cost estimates a 19.5% saving could be realised by using Wadiso optimization software as compared to the traditional trial and error.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering in the School of Civil & Environmental Engineering, in 2024.
Keywords: Performance assesment; Water distribution network; Trial and error; Partial enumeration; Wadiso; EPANET; Wadiso; UCTD